FDI determination and corporate tax competition in a volatile world - Mauro Ghinamo; Paolo M. Panteghini; Federico Revelli (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper investigates the role of economic and political volatility in the process of corporate tax-rate determination. The article is based on a theoretical framework that allows for the ability of multinational firms to choose the optimal timing of foreign investment and to shift profits by transfer pricing, and provides an empirical analysis on a large panel data set of countries over the 1983-2003 period. First, a reduced-form dynamic equation of corporate tax rate determination is estimated by the generalised method of moments (GMM), where a country's top statutory corporate tax rate depends on a number of measures of economic and political volatility. The fundamental testable prediction derived from the theoretical model is that increased volatility should reduce a country's corporate tax rate. Our results support the hypothesis that economic volatility is associated with lower top statutory corporate tax rates, while our measures of political volatility have no significant impact on corporate taxation policy. In order to identify the channels through which volatility works, we also estimate a structural model allowing for simultaneous determination of the corporate tax rate and the inflow of FDI to a particular country. The estimates of the structural model show that economic volatility affects the corporate tax setting process through their impact on FDI inflow.
Keywords: C23; F23; H87; 330; Direktinvestition; Körperschaftsteuer; Steuerwettbewerb; Standortfaktor; Wirtschaftliche Instabilität; Politische Stabilität; Schätzung; Welt